Forming of ecological awareness of rural communities through the use of information by the local government - Stoczkowska, Renata; Obrębska, Maria; Kowalski, Ryszard (Studia Ecologiae et Bioethicae, 2007)
Access to information about the state of environment and action taken by local government on its behalf is an important element influencing participation of citizens of rural areas. The aim of this research was to check if the local government of the chosen communes of East Mazowsze makes it possible for the citizens to gain access to information using the internet. 58 internet sites of the chosen communes of East Mazowsze were analysed, the research showed big differences in the use of internet as to the contents and technical abilities of said communes, they do not fully utilize the possibility to publish information on the internet and with that the ability to communicate with the others.